The Discrete Load Frequency Control System Using a Robust Periodic Output Feedback Controller. (17th April 2023) - Kumawat, Hukam Chand; Bhadu, Mahendra; Kumar, Arvind; Mahela, Om Prakash; Khan, Baseem; Anand, Divya; Breñosa, Jose
Abstract : The load frequency control (LFC) is a most important tool for the frequency regulation mechanism in the widely spread modern power system. The LFC system consists of a communication structure to transmit the measurement and control signal. Usually the controllers in LFC systems are designed and implemented in continuous mode of operation. This article investigates the discrete mode load frequency control (LFC) mechanism, by employing the concept of the periodic output feedback (POF)-based controller with varying input and output sampling frequencies. Both the optimal sampling frequency and the optimal POF controller gain matrix are found by using the particle swarm optimization (PSO) method. The POF-based controller is intended for usage in two-area multisource LFC systems, with varying input and output sampling frequencies. The performance analysis takes into account a variety of scenarios, including those without a conventional stabilizer, with conventional continuous and corresponding discrete mode PSS, and a proposed discrete mode POF controller. Furthermore, the efficacy of the discrete mode POF controller is evaluated on the MATLAB/Simulink platform.